A study on the factors governing retailer-customer long-term relationship. Issue 3 (19th August 2014) - Deb, Madhurima; Ali, Abbas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The prime objective of the study is to develop a comprehensive model of retailer-customer relationship. Design/methodology/approach Data was collected using questionnaire administered at organized grocery retail outlets in India. Total of 612 customers were surveyed. Findings Empirical evidence suggests that perception of merchandise quality depends upon perception of quality of services. It is also found that apart from store level attributes customer level attributes also play important role in retailer-customer long-term relationships. Practical implications Retailers would be benefitted by the in-depth knowledge of factors that determine long-term relationships with customers. The finding of the study implies that efforts of retailers to retain customers should be directed towards right set of customers. In the present study details about customer level attributes will benefit retailers to target right set of customers. Academicians would be benefitted by developing in-depth understanding about different store level and customer level attributes that determine retailer-customer long-term relationship. Originality/value The model developed in this study depicts the impact of retailer's effort as perceived by customers and customer's values, on commitment. There are very few studies in this area in the context of grocery retail which has taken customer level attributes that motivates them to develop long-term relationships. Coming to Indian context very little work is being done.